FORMULATION AND EVALUATION OF FAST DISSOLVING FILM OF LORNOXICAM - Jassim, Zainab E; Mohammed, Mais F; Sadeq, Zainab Ahmed (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the present work was to formulate and evaluate fast dissolving film containing lornoxicam. Materials and Methods: To prepare the film, hydroxypropyl methylcellulose E5 and polyvinyl alcohol (PVA) were used as film-forming polymers by solvent casting method. Glycerine was used as plasticizer, aspartame, and mannitol as sweetener. All prepared films were evaluated for its weight variation, disintegration time, thickness, drug content, pH, dissolution study, and folding endurance. The drug-excipients compatibility study was done using differential scanning calorimetry (DSC) and Fourier transform infrared (FTIR). Results: Satisfactory results obtained when PVA was used as film-forming polymer, and the drug was dispersed in the polymer solution using poloxamer 407 as a solubilizing agent. Formulation F2 is considered as the optimized formulation as it showed good folding endurance (>300), faster disintegration rate (30 s), and maximum in vitro drug release (87%) within 5 min. DSC and FTIR studies showed no interaction between drug and the polymers. Conclusion: It can be concluded from the study that the fast dissolving film can be prepared for poorly water-soluble drug lornoxicam using PVA as a suitable film-forming polymer.